Mass measurements of neutron-rich gallium isotopes refine production of nuclei of the first $r$-process abundance peak in neutron-star merger calculations - Reiter, Moritz Pascal; Ayet San Andrés, S.; Nikas, S.; Lippuner, J.; Andreoiu, C.; Babcock, C.; Barquest, B. R.; Bollig, Julian; Brunner, T.; Dickel, T.; Dilling, J.; Dillmann, I.; et al. (Physical review, 2020)
We report mass measurements of neutron-rich Ga isotopes 80−85Ga with TRIUMF's Ion Trap for Atomic and Nuclear science. The measurements determine the masses of 80−83Ga in good agreement with previous measurements. The masses of 84Ga and 85Ga were measured for the first time. Uncertainties between 25 and 48 keV were reached. The new mass values reduce the nuclear uncertainties associated with the production of A≈84 isotopes by the r-process for astrophysical conditions that might be consistent with a binary neutron star (BNS) merger producing a blue kilonova. Our nucleosynthesis simulations confirm that BNS merger may contribute to the first abundance peak under moderate neutron-rich conditions with electron fractions Ye=0.35−0.38.
Gesehen am 02.04.2020